MASF: Modelo de Referência para Aplicação da Sequência Fedathi na formação profissional e na produção de conteúd - Cardoso, Rafaela Ponte Lisboa (2015)
The aPClications of Fedathi sequence (SF), that is, its uses in education bring many possibilities for expansion of this teaching methodology, fostering a growth perspective just beyond its phases: taking a stand, maturation and debruçamento, solution and proof. Placing it as an alternative to an education perspective, whose teacher is the mediator and the student, an active subject, participatory, critical, both integrated in the teaching-learning process. Thus enhancing the SF uses in Mathematics Education, Distance Learning, production of educational videos, teacher training, for example. This work aims to identify concepts adhering to SF for training professionals and content production, defining strategies oriented strategies, artifacts and goals. Therefore, we used as research methods systematic review of literature on the aPClications of SF; case studies related to the production of content to investigate the use of SF in the scenarios of production and training; and case studies in a higher education institution to validate the MASF in the model institutionalization perspective, defined as the contribution of labor. Among the results, we present a pedagogical reference model to guide professionals and / or educational institutions in the definition, implementation and improvement of the SF using processes for the production of educational content and the training of professionals to act in teaching situations participatory-learning. In the face of this study, we can see how the MASF from the structuring of an educational model can promote the widespread adoption of SF regarding the content production process, teacher training and institutionalization of SF.